Modernization of the Investor-State Dispute Settlement System: reform or revolution? - I. M. Lifshits; A. V. Shatalova (Московский журнал международного права, 2023)
INTRODUCTION. The UN Commission on International Trade Law established Working Group III in 2017. Within the framework of this Working Group, States’ delegations and representatives of international governmental and non-governmental organizations seek to work out solutions to the identified problems of the investor-State dispute settlement system. Such problems include: lack of consistency and predictability of arbitral awards, lack of independence and impartiality of arbitrators, cost and duration of proceedings. Part of the ways suggested by the UNCITRAL Secretariat and States to remedy problems could be estimated as reform of the system, but several proposals seem to be a revolution.MATERIALS AND METHODS. The authors researched the provisions of bilateral investment treaties, case law of tribunals demonstrating the problems of the ISDS system, as well as the works of Russian and foreign scholars. The methodological basis of the research contains general scientific and special methods.RESEARCH RESULTS. The authors have analyzed several ways of the ISDS system reform overviewed by the Working Group III. Firstly, the authors have considered the draft code of conduct for arbitrators, provisions on third-party funding and an advisory center in the ISDS system. It has been stated that each of these initiatives is able to solve certain problems of the system. Secondly, the authors have analyzed the documents on the creation of an appellate mechanism and a standing multilateral mechanism for the settlement of investment disputes. The authors have concluded that initiatives may bring the fundamental changes to the system.DISCUSSION AND CONCLUSIONS. The authors have concluded that the identified shortcomings of the ISDS system can be remedied only by its reform. Every problem of the system can and should be rectified through consistent work, and not by radical changes. The revolutionary ways considered, such as the appellate instance and the court, not only will not solve existing problems, but rather will add new ones. For example, such a “revolution” of the system may result in establishment of the two parallel regimes of investorstate dispute resolution.